Review of Plug-Based Load Energy Management Systems (PLEMS) for energy and comfort management of buildings - Amin, F.B.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
The global energy consumption has risen significantly for the last few years that contributed to the large amount of Carbon Dioxide (CO2). Plug-based load equipments has been identified as one crucial component of whole-building energy use. This paper reviews the goals of PLEMS, along with related definitions, classification of PLEMS equipments and PLEMS control systems. A number of previous research that directed to PLEMS along with building sector, objectives, control systems, algorithm and simulation tools are also presented in this paper. The reviews indicate that it is essential to improve plug-based load equipments efficiency standards. Classification of these electrical devices according to their consumption patterns would facilitate energy wastage analysis and predictions of future consumption patterns. The application of intelligent control systems into PLEMS could lead to significant energy savings. Â© 2015 IEEE.